Phase Noise Analys is of Voltage-Controlled Oscillator - Wang, Jing Yuan (My University, 2009)
In modern wireless communication technology, designing low power, high frequency transceivers while exhibiting low noise is still one of the challenging topics in RF systems. Compared to other technologies, CMOS VCO has a poorer performance at phase noise measurements. Therefore, improving phase noise becomes a very important issue in designing a high quality YCO.
This work describes and compares the available models to realize low phase noise oscillators. On this basis, the possible criteria for reducing phase noise are discussed.
In this thesis, we explore phase noise fluctuations at the offset range of 10kHz to lOOK Hz for six 2.4 GHz LC-tuned YCOs, fabricated in O.18μm standard mixed-signal CMOS process. We compare the phase noise performance of all six circuits and draw conclusions about reducing phase noise.
The measurement results show that the Q factor of the inductor has the most significant effect on reducing phase noise fluctuations. The next important parameter is the capacitor. The resistors in the VCO do not affect phase noise fluctuations.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering